First-principles study on the synergistic effects of codoped anatase TiO2 photocatalysts codoped with N/V or C/Cr - 许文慧 马新国 吴桐 贺之琦 王辉虎 黄楚云 (半导体学报：英文版, 2014)
An effective compensated codoping approach is described to modify the photoelectrochemical prop- erties of anatase TiO2 by doping with nonmetals （N or C） and transition metals （V or Cr） impurities. Here, com- pensated codoped TiO2 systems are constructed with different dopant species and sources, and then their dopant formation energies and electronic structures are performed to study the stability and visible-light photoactivity by first-principles plane-wave ultrasoft pseudopotential calculations, respectively. The calculated results demonstrate that the codoping with transition metals facilitates the enhancement of the concentration of p-type dopants （N and C） in a host lattice. Especially, compensated codoping not only reduces the energy gap, to enhance the optical ab sorption, and eliminate the local trapping, to improve carrier mobility and conversion efficiency, but it also keeps the oxidation-reduction potential of the conduction band edge. These results are conducive to the understanding of the synergistic mechanism of the photocatalytic activity of TiO2 that is enhanced by codoping.